Visual cortex responses to suprachoroidal electrical stimulation of the retina: effects of electrode return configuration - Cicione, Rosemary; Shivdasani, Mohit; Fallon, James; Luu, Chi; Allen, Penny; Rathbone, Graeme; Shepherd, Robert; Williams, Chris (IOP Publishing Ltd, 2012)
A clinically effective retinal prosthesis must evoke localized phosphenes in a retinotopic manner in response to stimulation of each of the retinal electrodes, evoke brightness cues over a wide dynamic range and function within safe stimulus limits. The effects of varying return configuration for retinal stimulation are currently unknown. To investigate this, we implanted a flexible, 7x12 electrode array into the suprachoroidal space of normally-sighted, anesthetized cats. Multi-unit activity in the primary visual cortex was recorded in response to electrical stimulation using various return configurations: monopolar vitreous (MPV), common ground (CG), hexagonal (HX), monopolar remote (MPR) and bipolar (BP_N). MPV stimulation was found to be the most charge efficient and was most likely to induce cortical activity within safe charge limits. HX and CG stimulation were found to exhibit greater retinal selectivity compared to the MPV return at the expense of lower cortical yield and higher P50 charge levels, while cortical selectivity was unaffected by choice of return. Responses using MPR and widely spaced BP_N configurations were similar to those using the MPV return. These results suggest that choice of return configuration for a retinal prosthesis will be balanced between resolution and stimulation within safe charge limits.